The black bone disease: a case report of ochronotic hip arthropathy - Rathi, Rahul; Garg, Shivam; ., Vishwas; Kumar, B. L. (International Journal of Research in Orthopaedics, 2022)
Ochronotic arthropathy is a rare complication in patients with alkaptonuria (AKU) that arises as a result of accumulation of ochronotic pigment in the joints. This case report presented a 70-year-old female patient with chronic pain in B/L knee and right hip with decreased e range of motion. The physical and radiographic findings were agreeable with end-stage hip osteoarthritis and knee osteoarthritis. The diagnosis was done by finding of a dark capsule and femoral head during the total hip replacement. The surgical treatments significantly minimized and enhanced the range of motion (ROM). AKU normally emerges after age 40 and is normally asymptomatic till the involvement of the spine, hip, knee and shoulder joints. Therefore, orthopedic surgeons must be observant of clinical manifestations of this rare condition, before and during the surgery. Arthroplasty is an appropriate therapeutic recourse for patients suffering from ochronotic arthropathy.